2018
DOI: 10.1002/rmb2.12084
|View full text |Cite
|
Sign up to set email alerts
|

Non‐esterified fatty acid‐associated ability of follicular fluid to support porcine oocyte maturation and development

Abstract: PurposeThe effect of supplementing maturation medium with follicular fluid (FF) was examined according to its non‐esterified fatty acid (NEFA) content or with a fatty acid mixture (FA‐Mix) on the developmental competence of oocytes, as well as the mitochondrial quality and quantity in the oocytes and cumulus cells.MethodPorcine oocytes from a slaughterhouse were used.ResultsThe FF or FA‐Mix in maturation medium increased the lipid content in both the oocytes and the cumulus cells, but the adenosine triphosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
(73 reference statements)
0
14
0
1
Order By: Relevance
“…Thus, basal rates of respiration and glycolysis in GCs from the control group were significantly reduced in the presence of FF from older women but FF from the young donors fail to improve the bioenergetic parameters in the ARA group (Figure 3). Recently, a porcine in-vitro maturation model showed that supplementing the maturation medium with FF not only increased mitochondrial DNA copy number and the ATP content in both oocytes and cumulus cells, but also the survival of cumulus cells and the blastulation rate (Ogawa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, basal rates of respiration and glycolysis in GCs from the control group were significantly reduced in the presence of FF from older women but FF from the young donors fail to improve the bioenergetic parameters in the ARA group (Figure 3). Recently, a porcine in-vitro maturation model showed that supplementing the maturation medium with FF not only increased mitochondrial DNA copy number and the ATP content in both oocytes and cumulus cells, but also the survival of cumulus cells and the blastulation rate (Ogawa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that fatty acids are ligands for PPARs to transcribe genes for mitochondrial fatty acid oxidation, and PPAR inhibition reduces fatty acid oxidation as well as lipolysis [8,42]. Furthermore, elevated concentrations of non-esterified fatty acids and glucose enhance lipid contents and reduce lipolysis and fatty acid β-oxidation [43,44]. Increased lipid contents were correlated with apoptosis in blastocysts [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, basal rates of respiration and glycolysis in GCs from the control group were significantly reduced in the presence of FF from older women but FF from the young donors fail to improve the bioenergetic parameters in the ARA group (Figure 3). Recently, a porcine in-vitro maturation model showed that supplementing the maturation medium with FF not only increased the mitochondrial DNA copy number and the ATP content in both oocytes and cumulus cells, but also the survival of cumulus cells and the blastulation rate [53].…”
Section: Discussionmentioning
confidence: 99%